(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
The seed latex of Hura crepitans (Linn.) has been used for managing various diseases in both humans and animals, including as an intestinal antiparasitic against nematodes and coccidia in sheep. This research aimed to evaluate the antiparasitic efficacy of H. crepitans seeds, determine the effective dose for this effect, and assess any potential toxic effects on fattening lambs and their impact on blood parameters. Six ewe lambs were administered different doses of H. crepitans seeds (ranging from 0.16 to 6 g/kg b. w.). The antiparasitic efficacy was assessed by measuring the presence of gastrointestinal parasites, oocysts per gram of feces (opg), and eggs per gram of feces (epg). No significant changes were observed in feed intake or body weight. Vital signs, blood parameters, and most biochemical variables evaluated (AP, GGT, and TP) remained stable, with no increases in AST, ALT, or LDH even at the highest doses (4 and 6 g/kg b. W.). The absence of significant adverse effects or alterations in the measured blood variables suggests that Hura crepitans seeds can be administered to lambs as a gastrointestinal antiparasitic at doses up to 6 g/kg b. w. without causing side effects.